Molecular recognition pattern of cytotoxic alkaloid vinblastine with multiple targets - Pandya, Prateek; Agarwal, Lokesh Kr; Gupta, Neelima; Pal, Sourav (Journal of Molecular Graphics & Modelling, 2014)
Vinblastine (VLB), a cytotoxic alkaloid is used extensively against various cancer types and the crystal structure of its tubulin complex is already known. Multitarget affinity of vinblastine has been investigated and the nature of binding with biological receptors namely, duplex DNA and Human serum albumin (HSA) has been compared to the binding characteristics of its known complex with natural high affinity receptor tubulin using molecular docking and QM-MM calculations. VLB is found to interact with DNA as well as HSA protein, though, with weaker affinity as compared to tubulin. Analysis of various docked complexes revealed that the H-bonds and cation-pi bonds do not have significant contribution to the binding interactions and despite its large size, VLB remains in relaxed conformation and fits in the hydrophobic regions on the receptors. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Drug-DNA interactions; Drug-protein binding; Human serum albumin; Molecular docking; Multitarget affinity; QM-MM calculation; Vinblastine